Is Guidance and Counselling Services Necessary in Elementary Schools? Literature Study of the Urgency of Guidance and Counselling in Elementary Schools - Aulia Rahma; Teofilus Ardian Hopeman; Windha Arum Anggraeni (The Eastasouth Journal of Learning and Educations, 2023)
The implementation of education is not spared from various problems that arise. As educational institutions, schools play an essential role in preventing and overcoming academic issues that may occur. Guidance and counseling are components that can be a way and help in solving these problems. This study aims to explain the role of guidance and counseling services and the urgency of their implementation in elementary schools. The research method used in this study is a literature study with data collection techniques through various research journals, books, online articles, encyclopedias, and other relevant and needed sources in this research which is then systematically compiled until data is collected and obtained. Based on the data and information that researchers have accepted, the researcher concluded that guidance and counseling services in elementary schools always need to be carried out by every class teacher considering their significant role and benefits to the development of students not only academically but also their attitudes and character to support their careers in the future. Therefore, class teachers must understand the concept of guidance and counseling services so that their implementation in elementary schools can be carried out optimally without significant obstacles.